International trade regulation and job creation - L. Alan Winters (IZA World of Labor, 2014)
Trade regulation can create jobs in the sectors it protects or promotes, but almost always at the expense of destroying a roughly equivalent number elsewhere in the economy. At a product-specific or micro level and in the short term, controlling trade could reduce the offending imports and save jobs, but for the economy as a whole and in the long term, this position has neither theoretical support nor empirical evidence in its favor. Given that protection may have otherâusually adverseâeffects, understanding the difficulties in using it to manage employment is important for economic policy.
Keywords: F16; F13; F66; 330; employment; tariffs; protection; trade regulation